Socialization Program for Prevention and Early Detection of Congenital Hearing Loss in the Families of Deaf School children - Gwenny Ichsan Prabowo; Citrawati Dyah Kencono Wungu; Retno Handajani; Nyilo Purnami; Fis Citra Ariyanto (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: socializing hearing loss examination and early detection to patients and their families in deaftype B schools. Methods: A community service program in the form of socialization was performed to thefamily of patients with hearing loss in deaf school type B, Surabaya, Indonesia. Pretest and posttest wereconducted to determine the initial understanding and post socialization knowledge of these people. We alsoasked the participants to fill on a questionnaire regarding the possible causes of the hearing loss (familyhistory, drug use, history of disease, and history of head trauma). Results: Based on the summary of pretestand posttest from the participants, an increase in participants’ knowledge of hearing lost was found. Thisactivity was attended by 90 family members of 37 patients with hearing loss. Pre and post test results. Theresults of the questionnaire showed that 94.59% of the patients came from Javanese ethnicity. As many as21.62% of patients had a family history of hearing loss, and even 2 patients had a father, mother, and siblingwith hearing loss. A total of 18.92% had a history of using ototoxic drugs, 16.22% had a history of maternalRubella infection during pregnancy, and 2.7% had a history of head trauma. Conclusion: Socializationprogram was effective to increase knowledge of congenital hearing loss for family of deaf schoolchildren.The result of the questionnaire showed that deaf schoolchildren had several risk factors for the occurrenceof hearing loss. Similar program can be performed in communities in other areas to increase prevention andearly detection of hearing loss in Indonesia.